The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ef1007819
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures of Asphaltenes Based on the Dissociation Reactions of Their Ions in Mass Spectrometry

Abstract: We report here an examination of the mass spectrometric fragmentation behavior of molecular ions generated (and excited) by electron ionization (EI) from several asphaltene model compounds simulating both the island and archipelago structural models. This behavior is compared to that of protonated molecules generated from the same compounds by atmospheric pressure chemical ionization (APCI) and excited by collision-activated dissociation (CAD). The fragmentation behavior of the protonated molecules and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
122
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 26 publications
(30 reference statements)
15
122
0
1
Order By: Relevance
“…Most importantly, L2MS studies have established the ability to disaggregate asphaltene nanoaggregates, [30] a known problem with some mass spectral techniques. Related mass spectral studies corroborate island molecular architecture [31,32]. In conceptually simple, robust, surfacetension studies, the PAH (polycyclic aromatic hydrocarbon) size for several asphaltene types has been confirmed [33,34].…”
Section: Introductionsupporting
confidence: 52%
“…Most importantly, L2MS studies have established the ability to disaggregate asphaltene nanoaggregates, [30] a known problem with some mass spectral techniques. Related mass spectral studies corroborate island molecular architecture [31,32]. In conceptually simple, robust, surfacetension studies, the PAH (polycyclic aromatic hydrocarbon) size for several asphaltene types has been confirmed [33,34].…”
Section: Introductionsupporting
confidence: 52%
“…According to Yen-Mullins model, asphaltene molecules are dominated by island architecture with most probable molecular weight of 750 Da, as supported by recent mass spectral analysis. [39][40][41] Approximately six asphaltene molecules form a nanoaggregate via -stacking of their PAH cores. The asphaltene nanoaggregates can further associate to form clusters with aggregation numbers of approximately eight.…”
Section: Asphaltenesmentioning
confidence: 99%
“…They comprise 63 the fraction of petroleum that is soluble in toluene but insoluble 64 in n-alkane [4] and can correspond to up to 20% of crude oil [5]. 65 The elucidation of the structures of the molecules in asphaltenes 66 has far reaching implications [3] since asphaltenes clog pipes used 67 for transportation of crude oil and poison catalysts used in refining 68 [1,[6][7][8][9][10][11]. Further, only few uses exist for asphaltenes, including 69 expensive upgrading to distillates [12], road construction [13] 70 and recently proposed use in organic electronic materials [14,15] [9] to be especially well suited for evaporation and ionization of 114 asphaltenes since it has no bias to more polar analytes and it pro-115 duces only one ion type, molecular ion (M +Å ), for all asphaltene 116 model compounds studied [9].…”
mentioning
confidence: 99%
“…These methods 120 allow for the determination of the molecular weight and elemental 121 composition of all analytes present. However, structural informa-122 tion can only be obtained via tandem mass spectrometry experi-123 ments wherein the molecular ions are isolated and subjected to 124 collision-activated dissociation (CAD) or other reactions [8,28]. 125 Previous studies on CAD of protonated asphaltene model com- 126 pounds have revealed useful structural information [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation